Charged residues in the C-terminal domain of apoA-I modulate oligomerization - Fuentes, Lukas A. (Biochemistry, 2018)
Charged residues of the C-terminal domain of human apolipoprotein A-I (apoA-I) were targeted by site-directed mutagenesis. A series of mutant proteins were engineered in which lysine residues (Lys 195, 206, 208, 226, 238, and 239) or glutamate residues (Glu 234 and 235) were replaced by glutamine. The amino acid substitutions did not result in changes in secondary structure content or protein stability. Cross-linking and size-exclusion chromatography showed that the mutations resulted in reduced self-association, generating a predominantly monomeric apoA-I when five or six lysine residues were substituted. The rate of phosphatidylcholine vesicle solubilization was enhanced for all variants, with a ~3-fold rate enhancement for apoA-I lacking Lys 206, 208, 238 and 239, or Glu 234 and 235. Single or double mutations did not change the ability to protect lipolyzed low density lipoprotein from aggregation, but variants lacking >4 lysine residues were less effective in preventing lipoprotein aggregation. ApoA-I mediated cellular lipid efflux from wild-type mice macrophage foam cells was decreased for the variant with five lysine mutations. However, this protein was more effective in releasing cellular phosphatidylcholine and sphingomyelin from Abca1-null mice macrophage foam cells. This suggests that the mutations caused changes in the interaction with ABCA1 transporters, and that membrane microsolubilization was primarily responsible for lipid efflux in cells lacking ABCA1. Taken together, this study indicates that ionic interactions in the C-terminal domain of apoA-I favor self-association, and that monomeric apoA-I is more active in solubilizing phospholipid bilayers.